A critical discourse analysis of Curriculum for Excellence implementation in four Scottish secondary school case studies. Issue 4 (4th July 2021) - Hardley, Stephanie; Gray, Shirley; McQuillan, Ruth
ABSTRACT: Improving the health and wellbeing (HWB) of children and young people has become a policy priority due to perceptions of decreased mental health and academic outcomes. This interest is seen in the Scottish education policy, Curriculum for Excellence (CfE); however, ambiguity around the term 'wellbeing' may hinder successful curriculum enactment. Drawing on Foucauldian theories, a critical discourse analysis was conducted on four secondary school case studies to analyse how discursive constructions of HWB were recontextualised at the local level. Analysis found that schools primarily conceptualised HWB as either teaching for achievement of predefined learning outcomes or teaching as a process for character development, and these competing curricular aims may constrain teachers' pedagogic autonomy and impede the more aspirational tenets of CfE policy. The findings point to the need for further clarification of CfE policy aims to better support implementation.